Integrating KANO and QFD Method in Improving Customer Satisfaction (Case study: PT. XYZ) - Larisang; Sanusi; Khairul Imam (Jurnal INOVATOR, 2023)
PT. XYZ is a private company engaged in the sale of vehicles and spare parts and also car service. The problem that occurs is the increment of customer complaints. This is very contradictory to the service received by the customer. The purpose of this research is to produce a service system required by customers that is able to give satisfaction to the customers. This study resulted in ten service attributes required by customers based on the Kano model categorization, namely: complete facilities, comfortable waiting room temperature, indoor and outdoor cleanliness, ease of contacting bookings, ease of getting service schedules, long waiting time for service advisors, length of service time, the suitability of work, condition of the vehicle after service, and ease of payment. This research has 9 attributes. Technical characteristics include the addition of an air conditioner, online booking service, preparing appointments, vehicle pick-up service, home service, express maintenance service, explaining the results of work carried out by service advisor (SA) officers, service advisor officers (SA) accompany customers during payment, Maintenance Reminder Appointment (MRA) officers follow up to customers